IMPROVEMENT OF CORPORATE MANAGEMENT SYSTEM OF ENTERPRISE - Cui Yawen; Baimukhambetov Yerkebulan (Foundations and Trends in Research, 2025)
Modern businesses operate in a highly competitive and rapidly changing economic landscape, as well as in globalized markets. Under these circumstances, an efficient corporate governance system becomes crucial, ensuring a balanced consideration of the interests of all parties involved: shareholders, management, employees, and partners. Corporate governance serves as a key instrument for enhancing the competitiveness, sustainability, and investment appeal of businesses[1]. The relevance of the research stems from the need to enhance corporate governance in today’s companies, which is linked to increasing demands for transparency, accountability, and management effectiveness. In recent years, particular attention has been given to adherence to corporate standards, implementation of digital technologies in management, and enhancing the role of boards of directors in strategic enterprise development. In emerging markets such as Kazakhstan and China, corporate governance is crucial for ensuring sustainable economic growth, attracting investments, and protecting investors’ rights. However, many companies in these markets face challenges related to a lack of corporate culture, inadequate control over management decisions, and ineffective top-level management incentives.